The effects of high energy radiation on the tensile properties of rubber toughened nanocomposites - Jamal, Nur Ayuni; Anuar, Hazleen; Abd Razak , Shamsul Bahri (Trans Tech Publications, Switzerland, 2011)
Composites based on high density polyethylene (HDPE), ethylene propylene diene monomer (EPDM) and Organically Modified Montmorillonite (OMMT) clays were made by melt compounding followed by compression molding. Mechanical properties, X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) were used to characterize the nanocomposites. The addition of clay, compatibilizer agent, Maleic Anhydride Polyethylene (MAPE) and irradiation technique, High Energy Electron Beam (EB) considerably improved the properties of nanocomposites. Tensile Strength and Modulus (MPa) were found to increase significantly with increasing clay content and decreasing as the clay content exceeds 4 vol%. The largest improvement in nanocomposite tensile properties occurred at clay loading of 4 vol% (2-8 vol%) with irradiation technique. The d spacings of the clay in nanocomposites were monitored using XRD and the extent of delamination was examined by TEM. TEM photomicrographs illustrated the intercalated and exfoliated structures of the nanocomposites with OMMT, MAPE and irradiation process.